2009
DOI: 10.1108/14635770910972414
|View full text |Cite
|
Sign up to set email alerts
|

A business excellence model for the hotel sector: implementation to high‐class Greek hotels

Abstract: Purpose -The purpose of this paper is to present the development of a business excellence model applicable in the hospitality industry. Design/methodology/approach -Two surveys using questionnaires were conducted: the first one for the development of the model's criteria and sub-criteria and the second one for the assessment of the criteria and sub-criteria weights. The model was tested on a number of Greek high-class hotels. Findings -Compared with other business excellence models the proposed model includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…The identification of TQM factors is of particular interest in hospitality services, where "the delivery of hotel services is qualitatively different from the delivery of other types of services, and this influences the way service is managed, delivered and perceived by the customer" (Crick and Spencer, 2011, p. 463). In addition, Politis et al (2009) concluded that most Greek hotels failed to implement most TQM principles. Thus, to gain a better understanding of TQM implementation in the hotel industry, the present study focuses on small-and mediumsized hotels operating all over Greece.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of TQM factors is of particular interest in hospitality services, where "the delivery of hotel services is qualitatively different from the delivery of other types of services, and this influences the way service is managed, delivered and perceived by the customer" (Crick and Spencer, 2011, p. 463). In addition, Politis et al (2009) concluded that most Greek hotels failed to implement most TQM principles. Thus, to gain a better understanding of TQM implementation in the hotel industry, the present study focuses on small-and mediumsized hotels operating all over Greece.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of hospitality adopted in this study is that of describing both the material and the technical nature of the hospitality industry services as well as the relationship between host and guest (Aramberri, 2001;Carboni & Janati, 2016;Causevic & Lynch, 2009). Research on the hospitality industry covers a wide range of sub-sectors, including hotels and accommodation (Lukanova, 2010;Politis, Litos, Grigoroudis, & Moustakis, 2009), food outlets and restaurants (Auchincloss et al, 2013;Ponnam & Balaji, 2014), airline services (Chen & Chang, 2005;Liou & Tzeng, 2007), coach services (Jain, 2011;Jen, Tu, & Lu, 2010) and the cruise industry (Skaalsvik, 2011;Sun, Fen & Gauri, 2014). Much of this research, however, has prioritised issues pertaining to general and secular notions of hospitality ahead of hospitality in a religious context.…”
Section: Introduction 1 Introductionmentioning
confidence: 99%
“…The tourism industry is one of the fastest growing sectors worldwide. It is often investigated through its relation to GNP, employment and other macroindicators (Politis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%